2016
DOI: 10.1111/2041-210x.12657
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of animal accelerometer data using hidden Markov models

Abstract: Summary Use of accelerometers is now widespread within animal biologging as they provide a means of measuring an animal's activity in a meaningful and quantitative way where direct observation is not possible. In sequential acceleration data, there is a natural dependence between observations of behaviour, a fact that has been largely ignored in most analyses. Analyses of acceleration data where serial dependence has been explicitly modelled have largely relied on hidden Markov models (HMMs). Depending on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
177
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(178 citation statements)
references
References 57 publications
0
177
0
1
Order By: Relevance
“…Coarse‐scale behavior identification, like the approaches demonstrated here, could be a first step in a hierarchical process of identifying fine‐scale behaviors (Leos‐Barajas et al, ). Several studies have been successful in distinguishing general behaviors, like the behaviors identified in this paper, but have been less successful in effectively classifying finer scale behaviors associated with prey capture, prey handling and self‐maintenance (Hammond et al, ; Ladds et al, ; Shamoun‐Baranes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Coarse‐scale behavior identification, like the approaches demonstrated here, could be a first step in a hierarchical process of identifying fine‐scale behaviors (Leos‐Barajas et al, ). Several studies have been successful in distinguishing general behaviors, like the behaviors identified in this paper, but have been less successful in effectively classifying finer scale behaviors associated with prey capture, prey handling and self‐maintenance (Hammond et al, ; Ladds et al, ; Shamoun‐Baranes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unlikely that the scale of these vertical excursions is large enough to allow classification at the daily time step. Therefore, we suggest that future studies either deploy more sophisticated tags which are capable of recording more refined information about the underlying movement process (e.g., accelerometers; Leos‐Barajas, Photopoulou, et al., ) or consider a nested hierarchical HMMs in which vertical and horizontal movements are recorded and classified at differing time scales (Leos‐Barajas, Gangloff, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed discussion of the differences in these two types of applications is provided in Leos-Barajas et al [2016]. While past studies on toothed whales have concentrated on the former type of application [Brown and Smaragdis 2009, Clemins and Johnson 2005, Miller and Isojunno 2013, the focus of this paper was on the latter.…”
Section: Discussionmentioning
confidence: 99%